A rapid design exploration framework under additive manufacturing process uncertainty - Xiong, Yi (2018)
Current computer-aided design (CAD) systems are not computationally efficient for exploring the growing design space of products manufactured with additive manufacturing (AM). A rapid method with sufficient fidelity is desired. Meanwhile, uncertainties within the additive manufacturing process should be adequately considered. This study presents a rapid design exploration framework which considers the additive manufacturing process uncertainty based on metamodels. The framework is demonstrated with a multi-material designed stiffness construct design case, with an embedded horseshoe structure, which is manufactured with projection-based stereolithography (SLA) process.